Lithium Niobate Perovskite as the Support for Silver Nanoparticles for Non-Enzymatic Electrochemical Detection of Glucose - Piñon-Balderrama, Claudia Ivone; Reyes-López, Simón Yobanny; Espinosa Cristobal, Leon Francisco; Manriquez-Tristan, Atenea; Maldonado-Orozco, Maria Cristina; Hernandez-Escobar, Claudia Alejandra; Zaragoza Contreras, Erasto Armando; Zaragoza Contreras, Erasto Armando (2024)
: Lithium niobate perovskite and silver nanoparticle-based nanocomposites (LNB:AgNPs) were explored for developing an electrochemical glucose sensor. The perovskite to silver nanoparticle ratios investigated were 4:1, 1:1, 1:2, 2:1, and 1:4. Among these, the 4:1 ratio, with the lowest silver content, demonstrated the most stable performance during glucose quantification via amperometry. The sensor’s response was evaluated measuring the current at a fixed potential of 0.7 V following the injection of 1 mM glucose with each addition. The calibration curve obtained from the recorded data exhibited a linear response within the 1 to 15 mM glucose concentration range, achieving a sensitivity of 2 µA/mM, a high correlation coefficient (R2 = 0.997), and a limit of detection (LOD) of 0.5 µM. The LNB4:1AgNP composite allowed taking advantage of the unique properties of both components in a balanced manner, maximizing the sensor performance in practical applications.